1996
DOI: 10.1021/es950552v
|View full text |Cite
|
Sign up to set email alerts
|

Enantiomeric Selectivity in the Environmental Degradation of Dichlorprop As Determined by High-Performance Capillary Electrophoresis

Abstract: The chiral herbicide dichlorprop (2,4-dichlorophenoxy-2-propionic acid), which is sold and applied as the racemic mixture, was observed to degrade completely in soil within 31 days, with a half-life of 6.6 d. Degradation occurred with enantiomeric selectivity, indicating biologically mediated reactivity as opposed to strictly abiotic degradation. The S-(−)-isomer degraded significantly faster (t 1/2 = 4.4 d) than the R-(+)-isomer (t 1/2 = 8.7 d); this is contrary to other published results that show selective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
95
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(97 citation statements)
references
References 37 publications
2
95
0
Order By: Relevance
“…It is well known that the degradation of chiral pesticides in soil is usually enantioselective, primarily due to the enantioselectivity of soil biological degradation processes (Buerge et al, 2006;Garrison et al, 1996;Kurt-Karakus et al, 2005;Li et al, 2006;Ramezani et al, 2010); however, information on factors influencing such enantioselective degradation is still scarce (Buerge et al, 2003;Garrison, 2006;Lewis et al, 1999;Romero et al, 2001;Tan et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that the degradation of chiral pesticides in soil is usually enantioselective, primarily due to the enantioselectivity of soil biological degradation processes (Buerge et al, 2006;Garrison et al, 1996;Kurt-Karakus et al, 2005;Li et al, 2006;Ramezani et al, 2010); however, information on factors influencing such enantioselective degradation is still scarce (Buerge et al, 2003;Garrison, 2006;Lewis et al, 1999;Romero et al, 2001;Tan et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The S-enantiomers of MCPP, DCPP and 2,4-D were preferentially degraded under aerobic conditions (Zipper et al, 1999). The S-(-)-DCPP degraded significantly faster (t 1/2 ) = 4.4 d) than the R-(+)-isomer (t 1/2 = 8.7 d) in soil (Garrison et al, 1996). No preferential degradation of the R-and S-enantiomers of MCPP and of DCPP took place in an aerobic field-injection experiment (Rugge et al, 2002, Jarman et al, 2005.…”
Section: Enantioselective Herbicidal Activity and Toxicity Of Herbicimentioning
confidence: 92%
“…The hydrolysis product [methyl 2-nitro-5-(2,4-dichlorophenoxy) benzoic acid] of bifenox methyl ester, another herbicide component of Foxtril, was detected in the soil samples taken at 17 and 31 d. The acetate separation buffer was 50 mM at pH 4.65 and was composed as follows: 0.05 M glacial acetic acid: 0.05 M sodium acetate, 1:1, v:v. The cyclodextrincontaining buffer for enantiomeric separation was prepared by dissolving TM--CD in the acetate separation buffer to a final concentration of 25 mM cyclodextrin. (Garrison et al, 1996) Fig. 3-3.…”
Section: Separation Of Chiral Herbicides By Czementioning
confidence: 99%
See 1 more Smart Citation
“…In theory, enantiomers have identical physical and chemical properties and abiotic degradation rates (Garrison et al, 1996), whereas their individual toxicity, biological activity, and microbial degradation rates have been shown to differ (Overmyer et al, 2007;Diao et al, 2010;Liu et al, 2012;Sun et al, 2012). Several studies have reported that ethofumesate enantiomers showed an enantioselectivity in biochemical processes.…”
Section: Introductionmentioning
confidence: 99%